2013
DOI: 10.1095/biolreprod.113.112235
|View full text |Cite
|
Sign up to set email alerts
|

YES1 Activation Elicited by Heat Stress Is Anti-Apoptotic in Mouse Pachytene Spermatocytes1

Abstract: Deregulated expression of protein tyrosine phosphorylation has been implicated in testicular response to different stimuli. Herein, YES1, a nonreceptor protein tyrosine kinase, was found to be significantly up-regulated in pachytene spermatocytes (PS) during early recovery from a transient testicular heat stress. Coculture of PS with Sertoli cells (SCs) could enhance the hyperthermia-induced YES1 activation, indicative of a positive regulation of the paracrine signaling. Moreover, SU6656, a selective YES1 inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 53 publications
1
15
2
Order By: Relevance
“…Our results showed that the local testicular heating caused a significant increase in the TUNEL‐positive cell numbers of round and elongated spermatids. Our results agree with prior reports (Lue et al., ; Yamamoto et al., ; Oldereid et al., ; Hikim et al., ; Zhang et al., , ; Merico et al., ; Jia et al., ; Paul et al., ; Kanter et al., ; Liang et al., ; Henning et al., ), in which heat stress resulted in the apoptosis of germ cells. But a little different from the report by Lue et al.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our results showed that the local testicular heating caused a significant increase in the TUNEL‐positive cell numbers of round and elongated spermatids. Our results agree with prior reports (Lue et al., ; Yamamoto et al., ; Oldereid et al., ; Hikim et al., ; Zhang et al., , ; Merico et al., ; Jia et al., ; Paul et al., ; Kanter et al., ; Liang et al., ; Henning et al., ), in which heat stress resulted in the apoptosis of germ cells. But a little different from the report by Lue et al.…”
Section: Discussionsupporting
confidence: 93%
“…In this study, a self‐made thermo‐controlled 42°C blanket was used in the local testicular heating group. Recently, several studies in a few animals suggested that testes exposed to above body temperature (40–43°C) cause apoptosis in germ cells, including mice (Merico et al., ; Paul, Teng, & Saunders, ; Liang, Dong, Zhao, & Li, ), rats (Yamamoto et al., ; Hikim et al., ; Jia et al., ), dogs (Henning et al., ) and monkeys (Zhang et al., , ). Several studies also confirmed that exposing testes to above body temperature affects normal spermatogenesis, sperm fertility and male fertility (Gnay et al., ; Ikeda et al., ; Gau et al., ; Li et al., ; Guo et al., ; Salces‐Ortiz et al., ; Xun et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…44 Briefly, sections were deparaffinaged, rehydrated to distilled water, and immersed in boiling citrate buffer for 10 min to retrieve antigen. After endogenous peroxidase activity had been blocked with 0.3% H 2 O 2 in methanol for 30 min, slides were incubated with the primary antibody diluted in PBS, at 4 °C overnight in a moist box.…”
Section: Methodsmentioning
confidence: 99%
“…The immunohistochemical staning was conducted as previously described [11,12]. Slides were incubated at 4°C overnight in a moist box with the rabbit anti-PATZ1 antibody (Santa Cruz Biotechnology, Shanghai, China) at a dilution of 1:100.…”
Section: Immunohistochemistry and Immunofluorescencementioning
confidence: 99%
“…For example, Patz1 is highly expressed in the pluripotent mouse inner cell mass compared with the nonpluripotent trophectoderm. Moreover, the Patz1 genomic region is bound by various important transcription factors (TFs), such as Oct4, M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT 11 Nanog, Sox2, Klf4, and c-Myc [5]. Considering that the capablility of differentiating to regenerate endothelial cell populations in ECFCs resembles the same important characteristic in stem cells, it will therefore be of great interest to test if endothelial PATZ1 modulates angiogenesis via regulating certain pluripotent pathways.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%